Biostimulants in the quality of habanero pepper fruits - Murillo Cuevas, Félix David; Cabrera-Mireles, Héctor; Adame-García, Jacel; Vásquez-Hernández, Andrés; Martínez-García, Adrián de Jesús; Luria Moctezuma, Rebeca (Revista Mexicana de Ciencias Agrícolas, 2021)
The production of habanero pepper is mainly done with chemical fertilization, which can be inefficient since much of the applied fertilizer is released into the environment and can often become unavailable to plants. One way in which the use of chemical fertilizers can be reduced and the absorption of nutrients by the crop can be improved is by using biostimulants in the fertilization of plants. The objective of the work was to evaluate three microbial biostimulants on seeds, seedlings and the quality of habanero pepper fruit under protected macro tunnel conditions. The work was carried out in 2021 at the Tecnológico Nacional de México, Úrsulo Galván campus. The habanero pepper seeds used were of the Jaguar variety provided by the Cotaxtla Experimental Field- National Institute of Forestry, Agricultural and Livestock Research. The treatments evaluated were: 1) T22®+mycorrhizae INIFAP®; 2) Mix®; 3) Genifix®; and 4) control. An evaluation of the treatments in seed germination, growth and biomass of seedlings and quality of habanero pepper fruits was carried out. There were no significant differences in seed germination, but in height and dry weight of seedlings at 20 days after inoculation, since the seeds inoculated with the biostimulant Genifix were the ones that reached the highest height and dry weight. In terms of fruit size and weight, the plants treated with the biostimulants produced significantly larger and heavier fruits than the control plants.
Keywords: Bacillus; Trichoderma; biofertilizers; vegetables